Penggunaan Teknologi Komunikasi dalam Mempertahankan dan Memperdalam Hubungan Interpersonal pada Era Digital - Syahputra, Dasa Syawal (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
The development of communication technology in this era is something that we must accept with all the consequences that occur behind it all. There are many positive things that Akita buses get by utilizing the presence of this communication technology, in addition to the negative things that are behind it. Many agencies/institutions have utilized this communication technology to facilitate their work, including Salam TV; who always use communication technology to delegate tasks to fellow employees. The benefits obtained due to the use of communication technology are greater than the harms. Among them is being able to cut the distance and time, but the message is still delivered as desired. Regarding the obstacles that occur, of course there are, but solutions to these obstacles can be given.